Beyond the Limit of Goldschmidt Tolerance Factor: Crystal Surface Engineering to Boost the α‐Phase Stability of Formamidinium‐Only Hybrid Inorganic–Organic Perovskites. Issue 8 (10th July 2021) - He, Junjie; Chu, Yanfang; Sun, Yuchen; Zhang, Rui; Li, Jing; Zhao, Lei; Zhao, Hongmei; Liu, Pengfei; Li, Song
Abstract : Hybrid inorganic−organic perovskites (HIOPs) have the widest absorption range and the highest power conversion efficiency. Among HIOPs, formamidinium lead iodide (FAPbI3 ) has a wider absorption range and better thermal and light stability. Unfortunately, the photovoltaic active α‐phase of FAPbI3 transforms into its δ‐phase within several hours in ambient environment. Although partly sublimation of FA + with smaller cations can stabilize α‐FAPbI3, the multication systems suffer cation segregation and phase separation in long‐term use. Herein, a crystal surface engineering strategy to stabilize α‐FAPbI3 is developed. It is found that even introducing 1 mol% carboxylate anion can drastically improve the phase stability and operational stability of α‐FAPbI3 in the ambient environment (r.h. 50%, 25 °C). After 1 month of exposure to air, the phase change of α‐FAPbI3 is negligible. A detailed study indicates that the introduction of carboxylate anions prevents the water corroding the crystal surface and relaxes the strain in the crystals by increasing orientation diversity. The improved operational stability of the HIOPs arises from the intrinsic stability of pure formamidinium recipe and the stronger hydrogen bond between formamidinium and carboxylate. It not only provides a perovskite material for high‐performance solar cells, but also deepens the understanding of the phase stability of HIOPs. Abstract : For the first time, the formamidinium cation‐only perovskite is stabilized by crystal surface engineering. It is revealed that the introduction of carboxylate anions protects the perovskite from erosion of water and relaxes the strain in the crystals due to eliminating the preference growth of the crystal in a (001) facet. The perovskite gives superior operational stability compared to a mixed cation system.